Em-cena-ação – mise-en-scène documental contemporânea : notas sobre a elaboração da cena a partir dos processos fílmicos Para que o mundo não esqueça (2019/20) de Pedro Bomba e 144 horas e alguns minutos roubados (2019/20) de Gladson Galego - Souza Junior, Gladson Cardoso de (2019)
This research sought to study the elaboration process of the contemporary documentary scene. The emphasis of the work was to investigate the theoretical-methodological procedures for the elaboration of mise-en-scène used by contemporary -independent directors in their daily professional life. The greater interest is in the relationship between the subject's camera and the person's character. In this sense, we sought to investigate how the knowledge and methods produced and / or practiced by independent filmmakers are articulated with the know-how of cinema theory, based on the approximation of methodological procedures and practices present in other areas of knowledge production. The attempt to verify the possible approximations and distances belonging to different fields, as well as, to observe in what measure these areas are influenced and / or denied by elaboration of the staging of the documentary was given from the process of realization of the movies “so that the world does not forget” (2019/20) of Pedro Bomba and 144 hours and some minutes stolen (2019/20) of Gladson Galego.